2004
DOI: 10.1038/sj.onc.1207392
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide cDNA microarray analysis of gene expression profiles in pancreatic cancers using populations of tumor cells and normal ductal epithelial cells selected for purity by laser microdissection

Abstract: To characterize molecular mechanism involved in pancreatic carcinogenesis, we analysed gene-expression profiles of 18 pancreatic tumors using a cDNA microarray representing 23,040 genes. As pancreatic ductal adenocarcinomas usually contain a low proportion of cancer cells in the tumor mass, we prepared 95% pure populations of pancreatic cancer cells by means of laser microbeam microdissection, and compared their expression profiles to those of similarly purified, normal pancreatic ductal cells. We identified 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 27 publications
7
193
0
1
Order By: Relevance
“…In pancreatic cancer, prior studies using gene microarray analysis and immunohistochemistry demonstrated that the b4 integrin subunit was upregulated when compared to normal pancreas and pancreatitis tissues 10,11,13 as well as associated with cases that presented with lymph node metastasis. 12 Furthermore, the potential role of the a6b4 integrin in metastasis is supported by studies in papillary thyroid carcinoma which suggested that the increased expression of the integrin b4 subunit in cancer lesions could play a role in the development of lymph node metastasis. 27 Certainly, the in vivo data coupled with extensive in vitro data suggest that the a6b4 is associated with the invasiveness and metastatic potential of late stage cancers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In pancreatic cancer, prior studies using gene microarray analysis and immunohistochemistry demonstrated that the b4 integrin subunit was upregulated when compared to normal pancreas and pancreatitis tissues 10,11,13 as well as associated with cases that presented with lymph node metastasis. 12 Furthermore, the potential role of the a6b4 integrin in metastasis is supported by studies in papillary thyroid carcinoma which suggested that the increased expression of the integrin b4 subunit in cancer lesions could play a role in the development of lymph node metastasis. 27 Certainly, the in vivo data coupled with extensive in vitro data suggest that the a6b4 is associated with the invasiveness and metastatic potential of late stage cancers.…”
Section: Discussionmentioning
confidence: 98%
“…The quest for such markers has led to the use of high throughput technology such as genetic profiling and proteomics. Recent studies that included the use of genetic profiling and immunohistochemistry suggested that the integrin a6b4 is selectively overexpressed in pancreatic adenocarcinomas, [10][11][12][13] thus providing evidence of the potential role of this integrin in pancreatic cancer progression.…”
mentioning
confidence: 99%
“…Although very little is known about FOXJ2, another class I member, FOXA1, is amplified and overexpressed in esophageal and lung cancer (Lin et al, 2002). Other FOX family members are implicated in basal cell carcinomas, pancreatic cancer and secondary acute myeloblastic leukemia (Hillion et al, 1997;Nakamura et al, 2004;Teh et al, 2002). The role of BRCA1 at this promoter is unknown and has not been demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…After amplified RNAs (aRNAs) were labeled with Cy3 or Cy5, respectively, we carried out hybridization between labeled aRNAs and cDNA microarray slides containing 36 864 spots and detected the signals. Expression of CDC20 in various cancer tissues and their corresponding normal tissues were examined by using data sets that were analysed previously (Ono et al, 2000;Kitahara et al, 2001;Okabe et al, 2001;Hasegawa et al, 2002;Kaneta et al, 2002;Kitahara et al, 2002;Nagayama et al, 2002;Okutsu et al, 2002;Kikuchi et al, 2003;Okada et al, 2003;Ashida et al, 2004;Jinawath et al, 2004;Nakamura et al, 2004;Nishidate et al, 2004;Ochi et al, 2004;Obama et al, 2005;Takata et al, 2005;Hirota et al, 2006;Taniwaki et al, 2006;Yamabuki et al, 2006). To select genes that were suppressed by p53 and upregulated in various cancer tissues, the following two criteria were used: (1) genes whose expression were more than threefold decreased by Ad-p53 and (2) genes whose expression were more than threefold increased in various cancer tissues compared with its corresponding normal tissues.…”
Section: Cdna Microarraysmentioning
confidence: 99%